Profile of Lower Limb Muscle Power in Pencak Silat Athletes of IPSI Pekalongan City - Wijaya, M. Riski Adi; Subekti, Nur; Widodo, Agung (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The study aims to analyze the lower limb muscle power profile of Pencak Silat athletes affiliated with IPSI in Pekalongan City in preparation for the Provincial Sports Week (PORPOV) in 2023. Anticipated is that this study will offer a deeper insight into the determinants that impact athletes' achievements in the realm of Pencak Silat competition. The study utilizes a survey research design with a quantitative descriptive approach. The study subjects consist of five athletes who qualified for the 2023 PORPOV. Data collection involves the use of a lower limb muscle power test, specifically the vertical jump test. The results of the vertical jump test for Pencak Silat athletes from IPSI in Pekalongan City indicate that 20% or one athlete falls above the average classification, 60% or three athletes fall within the moderate classification, and 20% or one athlete falls below the average classification. The findings of this study reveal that about 80% of the lower limb muscle power component possessed by the athletes hasn't reached the classification above the average. The research's conclusion offers valuable insights into the factors affecting Pencak Silat athletes' performance, providing a basis for improving training programs to boost the achievements of IPSI-affiliated athletes in Pekalongan City.